Excess of NPM-ALK oncogenic signaling promotes cellular apoptosis and drug dependency - Ceccon, Monica (Oncogene, 2015)
Most of Anaplastic Large Cell Lymphoma (ALCL) cases carry the t(2;5; p23;q35) that produces the fusion protein NPM-ALK. NPM-ALK deregulated kinase activity drives several pathways that support malignant transformation of lymphoma cells. We found that in ALK-rearranged ALCL cell lines NPM-ALK was distributed in equal amounts between the cytoplasm and the nucleus. Only the cytoplasmic portion was catalytically active in both cell lines and primary ALCL, whereas the nuclear portion was inactive due to heterodimerization with NPM1. Thus, about 50% of the NPM-ALK is not active and sequestered as NPM-ALK/NPM1 heterodimers in the nucleus. Overexpression or re-localization of NPM-ALK to the cytoplasm by NPM genetic knock-out or knock-down caused ERK1/2 increased phosphorylation and cell death through the engagement of an ATM/Chk2 and γH2AX mediated DNA damage response. Remarkably, human NPM-ALK amplified cell lines resistant to ALK tyrosine kinase inhibitors (TKIs) underwent apoptosis upon drug withdrawal as a consequence of ERK1/2 hyperactivation. Altogether, these findings indicate that an excess of NPM-ALK activation and signaling induces apoptosis via oncogenic stress responses. A “drug holiday” where the ALK TKI treatment is suspended could represent a therapeutic option in cells that become resistant by NPM-ALK amplification.